(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
Fifty-three agricultural soil samples have been collected within the boundary of Dubz District, Lower Zab River Basin, Northeastern Iraq, between latitudes 35°30’0’’–35°50’0’’ N and longitudes 43°48’41’’–44°16’6’’ E. This study focuses on determining the concentration values and distributions of Co, Cu, Ni, Cr, Zn, Cd, Pb, As and Mn using the ICP-MS analytical technique to assess the environmental influences of these metals in soil samples by several pointers including the contamination factor (Cf), degree of contamination (Cdeg), potential ecological risk (Er), risk index (RI), toxic units (TUs) and the adverse effect index (AEI). The findings indicate that the values of these metals are arranged in descending order as follows: Mn> Ni> Cr> Zn> Cu> Co> Pb> As> Cd > Co > Cu > Zn > Pb > Cd > Ni > Cr > Mn > As. Except for As and Cd, the majority of the elements have values lower than the Earth’s crust average. The level of Co, Cr, Ni, Cu, Zn, Pb, and Mn contamination is low, whereas the contamination level of Cd is moderate, and As is considerably contaminated. Based on the results of ecological risk and potential risk index (RI), heavy metals indicate a low ecological risk of these metals in all collected soil samples. Depending on the values of the Adverse Effect Index (AEI) for Ni, Cr, Cu, and Mn, most of the studied agricultural soil samples indicate a probable effect on biota due to the concentration of these metals being high enough to affect the organisms negatively. Whereas the total toxic units (∑TUs) for all the sites indicate that the depositional and behavioral forms in the studied soils indicate a moderate toxicity of heavy metals to the ecosystem.